ROLE OF ARMS EXPORTS FROM UKRAINE ESCALATION OF ARMED CONFLICT IN THE MODERN WORLD - Кіт, О.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2012)
Attempt to determine the role Ukrainian arms exports within of some armed conflicts of modernity. As an example, three armed conflicts were considered : The civil war in Sri Lanka, the Macedonian conflict in 2001, and the Georgian-Ossetian conflict in 2008. Proved that the export of military goods from Ukraine may significantly influence the course and result of the armed conflict in the recipient State.